N-type photovoltaic cell re-claim qualification using cleaning process - Rahimi, Roslina Aida (2022)
Yield loss reduction is one of the continuous actions applied in the manufacturing industry to minimize overall operational costs. This study will focus on improving top defects from the diffusion process in the solar industry. In the diffusion process, scratches on the wafer surface are one of the top Pareto for scrap. One of the opportunities to improve the scrap is the cleaning and removing the diffusion layer back to its original condition before the diffusion process. The objective of the study is to study the cleaning recipe for removing the diffusion layer. Selected recipes will be qualified using reliability testing to ensure no additional impact on the product quality. The qualified cleaning recipe and the process will be validated and compared with the standard production wafer in terms of photovoltaic cell Power Conversion Efficiency, Electrical and Cosmetic Yield performance. This study uses the closed interval method in selecting the HFO3 parameter range for the cleaning recipe and qualified using Autoclave HAST chamber (ACL) and Reverse Biased Test Dielectric (RBTDE) reliability testing to confirm the product performance is fulfilling the standard specification. The statistical analysis in this study uses JMP software and analysis conducted using t-Test, Wilcoxon Test and Mosaic Plot distribution to ensure the rework wafer quality and performance comparable with the existing production wafer. The selected cleaning recipe observed that the combination parameter of 250ml HFO3 volume dosing and temperature of 70oC HFO3 bath showed the closest value to the existing product, which is control data. The Reliability testing result of the selected cleaning recipe passed and qualified under RBTDE and ACL tests which showed a probability value of 0.6494 for 0 hour, 0.4695 for 120hour and 0.6150, respectively, defined as an insignificant difference from the control product data. A higher volume run of the selected cleaning recipe was validated as well, which resulted better mean value at 22.94% for Power Conversion Efficiency and a higher Bin A percentage for Cosmetic Yield with a p-value of <0.0001 while the insignificant difference of Electrical Yield probability value of 0.8177 from control data. The implementation of the cleaning recipe for the diffusion layer rework process can improve the yield loss and, at the same time, benefit the industry due to the lower operational cost from the scrap reduction.